Retrospective Assessment of Factors Affecting Carboxyhemoglobin Levels in Patients Undergoing Robotic Surgery - Selin Erel; Özge Erkoçak; Ülgen Öztürk Toyran; Gözde İnan (Gazi Medical Journal)
Objective: Electrocautery in laparoscopic surgeries converts abdominal carbon dioxide gas into carbon monoxide, which binds to hemoglobin with a higher affinity than oxygen and can impair oxygen transport and lead to hypoxia. This study aimed to assess changes in carboxyhemoglobin (COHb) levels and investigate the factors affecting COHb levels in patients undergoing robotic surgery. Methods: Forty-two patients were included in this retrospective study. Patient demographics, anesthetic used, airway pressures, and COHb levels at different time points (baseline COHb-1st hour COHb-post-pneumoperitoneum COHb-postoperative care unit COHb-deltaCOHb) were considered. Age, gender, American Society of Anesthesiology (ASA) physical score, body mass index, smoking status, surgery type, anesthesia type, patient position, fresh gas flow (FGF), insufflation, and airway pressures, which may have an effect on COHb levels, were compared. Results: No significant relationship was found between COHb levels at all measured time points and factors such as gender, ASA scores, surgery type, anesthesia type, position, FGF, insufflation pressure, and airway pressure. Smokers had significantly higher COHb levels than passive smokers, non-smokers, and ex-smokers at baseline (p=0.003), 1st hour (p=0.006), and post-pneumoperitoneum COHb (p=0.009) levels. Conclusion: Long surgery time, use of different types of anesthetics, and low FGF does not increase the risk of elevated COHb levels. Hence, different anesthetic drugs and low FGF, regardless of the position of the patient or the length of the procedure, can be used in robotic surgery without increasing the risk.